Experimental investigation of UAV rotor aeroacoustics and aerodynamics with computational cross-validation - Kostek, A.A.; Lößle, F.; Wickersheim, R.; Keßler, M.; Boisard, R.; Reboul, G.; Visingardi, A.; Barbarino, M.; Gardner, A.D. (My University, 2022)
The study provided a base of comparison of known computational techniques with different fidelity levels for performance and noise prediction of a single, fixed-pitch UAV rotor operating with varying flight parameters. The range of aerodynamic tools included blade element theory, potential flow methods (UPM, RAMSYS), liftingline method (PUMA) and Navier-Stokes solver (FLOWer). Obtained loading distributions served as input for aeroacoustic codes delivering noise estimation for the blade passing frequency on a plane below the rotor. The resulting forces and noise levels showed satisfactory agreement with experimental data, however differences in accuracy could be noticed depending on the computational method applied. The wake influence on the results was estimated based on vortex trajectories from simulations and those visible in Background Oriented Schlieren (BOS) pictures. The analysis of scattering effects showed that influence of ground and rotor platform on aeroacoustic results was observable even for low frequencies.